TRANSCRIPT-BASED REFLECTION OF ONLINE LEARNING ON 8 TH GRADE STATISTICS AT SMPN 2 TANJUNGSARI - Leni Yulianingsih; Sumar Hendayana; Sofwan Gozali (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
Government of Indonesia has cancelled the face-to-face learning process at schools in since March 2020 Covid-19 pandemic. However, the learning process must go on to facilitate student learning. Online learning through Zoom is a solution for supporting student learning in the Covid-19 pandemic. The this study aims to obtain information of student learning on  statistical concepts (mean, median and mode) and statistical at 8 grade junior high school students as a selfreflection for improvement of subsequent learning. Data were collected through written tests and videoZoom recording during online learning. The video zoom recording was transcript for further analysis to obtain information of student speech.Number of the speech characters of teachers and students are presented in bar graphs for further analysis of learning tendencies. Written test was analysis to obtain information of student understanding on statistics concept. It was found that 95% of students can answer the written test correctly. Based on the analysis of the transcript data, it was found that learning tends to be teacher-cantered. Teacher realized that  does not give students the opportunity to express their opinion, the sequence of the discussion. This article describes a plan for improving the learning Keywords: Pandemic, Online, Learning Transcripts, Statistics